Non-front-fanged colubroid snakes: a current evidence-based analysis of medical significance. - Weinstein, SA; White, J; Keyler, D; Warrell, D (2013)
Non-front-fanged colubroid snakes (NFFC; formerly and artificially taxonomically assembled as "colubrids") comprise about 70% of extant snake species and include several taxa now known to cause lethal or life threatening envenoming in humans. Although the medical risks of bites by only a handful of species have been documented, a growing number of NFFC are implicated in medically significant bites. The majority of these snakes have oral products (Duvernoy's secretions, or venoms) with unknown biomedical properties and their potential for causing harm in humans is unknown. Increasingly, multiple NFFC species are entering the commercial snake trade posing an uncertain risk. Published case reports describing NFFC bites were assessed for evidence-based value, clinical detail and verified species identification. These data were subjected to meta-analysis and a hazard index was generated for select taxa. Cases on which we consulted or personally treated were included and subjected to the same assessment criteria. Cases involving approximately 120 species met the selection criteria, and a small subset designated Hazard Level 1 (most hazardous), contained 5 species with lethal potential. Recommended management of these cases included antivenom for 3 species, Dispholidus typus, Rhabdophis tiginis, Rhabdophis subminiatus, whereas others in this subset without commercially available antivenoms (Thelotornis spp.) were treated with plasma/erythrocyte replacement therapy and supportive care. Heparin, antifibrinolytics and/or plasmapheresis/exchange transfusion have been used in the management of some Hazard Level 1 envenomings, but evidence-based analysis positively contraindicates the use of any of these interventions. Hazard Level 2/3 species were involved in cases containing mixed quality data that implicated these taxa (e.g. Boiga irregularis, Philodryas olfersii, Malpolon monspessulanus) with bites that caused rare systemic effects. Recommended management may include use of acetylcholinesterase inhibitors (e.g. neostigmine) and wound care on a case-by-case basis. Hazard level 3 species comprised a larger group capable of producing significant local effects only, often associated with a protracted bite (eg Heterodon nasicus, Borikenophis (Alsophis) portoricensis, Platyceps (Coluber) rhodorachis). Management is restricted to wound care. Bites by Hazard level 4 species comprised the majority of surveyed taxa and these showed only minor effects of no clinical importance. This study has produced a comprehensive evidence-based listing of NFFC snakes tabulated against medical significance of bites, together with best-practice management recommendations. This analysis assumes increasing importance, as there is growing exposure to lesser-known NFFC snakes, particularly in captive collections that may uncover further species of significance in the future. Careful and accurate documentation of bites by verified species of NFFC snakes is required to increase the evidence base and establish the best medical management approach for each species.